Processo de desenvolvimento de produtos na indústria de revestimentos cerâmicos: estudo de caso em fabricantes que utilizam o processo de moagem a úmido, de moagem a seco e colorifícios. - Romachelli, João Celso (2005)
The increase of the competitiveness in the markets, demand products with high quality and that they are developed of form the one that the companies present fast cycle of development, high performance, and low cost. Some tools of the production engineering are available of form to optimize and to become more previsible the happened results of the process of development of products. An important aspect in the PDP, is the possible contribution of the supplier, combining itself since the stages initiates, of form to optimize performance ace characteristic, to reduce risks and to optimize the innovative process. The ceramic tiles industry Brazilian particularly can be characterized by producers that use water process and dry process. The industry that uses the dried milling process has grown of significant form from the beginning of years 90, producing currently about 60% of the national production. The ceramic tiles industry historically uses the supplier as collaborating in the development of products. In Brazil more specifically the role played for the suppliers of inputs for ceramic glazes is important. Considering itself that the common suppliers are ace industries that use the dry process and the water process, this work effects an exploratory boarding on the process of development of products in the ceramic tiles industry. Case studies were done in seven companies tiles manufacturers and three glazes suppliers. One concludes that the industry independently of the competitive strategy, must structuralize and co-ordinate better the PDP preventing the extreme dependence of suppliers. And that the established scene privileges more than proportionally, the industry that uses dry process.